BMP4 Promotes EMT and Mesodermal Commitment in Human Embryonic Stem Cells via SLUG and MSX2. (19th February 2014) - Richter, Anne; Valdimarsdottir, Lena; Hrafnkelsdottir, Helga Eyja; Runarsson, Johann Frimann; Omarsdottir, Arna Run; Oostwaard, Dorien Ward-van; Mummery, Christine; Valdimarsdottir, Gudrun
Abstract: Bone morphogenetic proteins (BMPs) initiate differentiation in human embryonic stem cells (hESCs) but the exact mechanisms have not been fully elucidated. We demonstrate here that SLUG and MSX2, transcription factors involved in epithelial–mesenchymal transitions, essential features of gastrulation in development and tumor progression, are important mediators of BMP4-induced differentiation in hESCs. Phosphorylated Smad1/5/8 colocalized with the SLUG protein at the edges of hESC colonies where differentiation takes place. The upregulation of the BMP target SLUG was direct as shown by the binding of phosphorylated Smad1/5/8 to its promoter, which interrupted the formation of adhesion proteins, resulting in migration. Knockdown of SLUG by short hairpin RNA blocked these changes, confirming an important role for SLUG in BMP-mediated mesodermal differentiation. Furthermore, BMP4-induced MSX2 expression leads to mesoderm formation and then preferential differentiation toward the cardiovascular lineage. Stem Cells 2014;32:636–648